TAKING VARIOUS AGRO-TECHNICAL MEASURES FOR THE PRESERVATION AND ACCUMULATION OF MOISTURE - M. B. Khalilov; A. F. Zhuk; A. A. Aytemirov; R. Kh. Gayrabekova (Юг России: экология, развитие, 2016)
ARTICLE RETRACTEDAim. The aim is to conduct a theoretical study of the conditions of occurrence of surface runoff and take technical measures for its prevention.Discussion. The occurrence of surface runoff is possible on condition that the intensity of moisture entry per time unit is greater than the intensity of its absorption and passage through the topsoil. Conditions of surface runoff occur at high intensity of moisture entering the soil surface which can be in the case of heavy rainfall, low water permeability of topsoil as a result of the increased density. The upper topsoil not affected by loosening passes moisture worse than loosened. Low water conductivity of the arable layer may be due to the fact that it is saturated with moisture up to the limit, and the underlying subsoil layers do not absorb or absorb not enough water, pass water less than enters through the upper topsoil. This phenomenon leads to oversaturation of the top plowed layer by water, which can lead to water erosion and landslide.Conclusion. We obtained analytical expressions describing the process of accumulation of moisture in the soil and the formation of surface runoff, which also allow to theoretically justify the need for different agronomic techniques impact on soil. We should select tools and soil impact techniques in order to preserve and accumulate moisture with account of the certain agrolandscape conditions specific to these fields.